Interactive multimedia: Hajjedu kiosk / Ilinadia Jamil and Zainal Kadir - Jamil, Ilinadia; Kadir, Zainal (2016)
and Previous researches and current initial findings . have shown that conventional approaches used in most Hajj supplementary learning materials are less effective in providing clear understanding to users, particularly the pilgrims. Most of the materials are based on passive learning. Thus, in order to cater for those limitations, this study proposed an idea of interactive multimedia approach in developing HajjEdu kiosk as an attempt to provide a better learning aid for supporting self-paced learning for Hajj. In addition, this study incorporates virtual environment (VE) and multimedia technology in designing the interface prototype as an attempt to persuade users especially hajj pilgrimage to use computer technology as their main supplementary learning material. Thus, this study elaborates the idea of publicly apply this application in every mosques for every states of Malaysia. Generally, this paper reviews some related literatures about Hajj, interactive multimedia technology, virtual environment and information kiosk. Lastly, this paper discusses on the results of the evaluation on the targeted users.